Strategi Pengembangan Sumber Daya Manusia Yang Profesional Dan Berdaya Saing Tinggi Pada Pt. Pln (Persero) Unit Pelaksana Proyek Kalimantan Bagian Barat - Melanno, Osta; Meitiana, Meitiana; Sintani, Lelo (Syntax Corporation, 2025)
Human resources are one of the strategic assets owned by every organization and need to be fostered, developed, and trained continuously. Professional and highly competitive workers are able to provide optimal performance and service to the community. This study aims to analyze and describe the implementation of HR development, the factors that influence it, and the strategies applied in the process at the West Kalimantan Project Implementation Unit 3 owned by PT. PLN (Persero). The location of the study is in Palangkaraya, Central Kalimantan. The approach used is descriptive qualitative with data analysis techniques through data reduction, data presentation, and drawing conclusions, and assisted by the Nvivo 12 Plus application. The results of the study indicate that the implementation of HR development includes: (a) identification of needs, (b) program planning, (c) program implementation, and (d) evaluation or feedback. The factors that influence HR development consist of: (a) organizational strategy, (b) employee needs, (c) implementation of development programs, and (d) leadership and management. The strategies implemented to create professional and competitive human resources include: (a) training and development programs, (b) providing certification, (c) employee welfare policies, and (d) leadership development.